People-Centered Development in The Aquarium Village Community - Madayani, Cindy; Ramdhani, Dzaky Kayungyun; Chanief, Ahmad Za'iimul (UI Scholars Hub, 2024)
Background: The changing landscape of Jakarta, especially in coastal areas, has sparked heated debates about spatial planning and social justice. Aims: This study aims to assess the extent to which the basic rights of the residents of Kampung Susun Akuarium are fulfilled, especially in terms of access to public facilities and other basic needs. Methods: The method used in this study is descriptive qualitative. Primary data were obtained through observation and in-depth interviews with residents and representatives of the Bangkit Mandiri Aquarium Cooperative. Secondary data were collected from relevant literature and previous research results. Results: Based on the documented interview results, these indicators were applied to assess the changes that occurred before and after the relocation. Before the relocation, residents of Kampung Akuarium faced forced evictions without adequate legal protection. Conclusion: The fulfillment of Sustainable Development Goals (SDGs) 11 in Kampung Akuarium showed some improvements and challenges.